Atividade de Demonstração Interativa (ADI): problematizando o estudo da difração e da interferência - Silva, Luiz da (2015)
This paper describes the production and the development of a proposal for a didactic sequence for teaching diffraction and interference of light on an enquiry-based approach. Its main feature is the adaptation of the methodology Interactive Lecture Demonstrations (ILD), in order to engage students in active inquiry. Unlike other approaches, this proposal consists of a methodological innovation by focusing the didactic transposition in the conceptual evolution of the students during the process of teaching and learning. It is developed upon a Vygotskian perspective, favoring the interaction between the actors in the process, contributing to a meaningful learning. A simple experimental apparatus was developed using a laser diode. The apparatus allows the observation of light diffraction by a hair. By means of the construction of a "cognitive conflict", the didactic sequence induces the discussion of the concepts involved in this curricular topic, without losing sight of the context and its application beyond the school environment. It was used an applet of the PhET - Physics Education Technology Project, in order to introduce the basics of waves and interference. The aim of the didactic sequence is the conceptual and experimental construction of the representation of light as a wave phenomenon. The theme is relevant, opening up possibilities for the introduction of modern physics topics in high school. It is a flexible sequence and it is easily adaptable to the reality of the school community. The proposal was applied on a secundary school and the analysis was done through research of students' answers to the questionnaire of the didactic sequence, direct observation of the student behavior during the activity, audio records and field diary and a quantitative analysis of the perception of students through an evaluation test of the didactic sequence.